PEMBUATAN MOLECULARLY IMPRINTED POLYMER (MIP) MELAMIN MENGGUNAKAN METODE COOLING-HEATING - Nurhamidah, Nurhamidah; Marinda, Popo; Koryanti, Erry; Royani, Idha (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Molecularly Imprinted Polymer (MIP) of melamine has been made using cooling-heating method. Melamine as the template is inserted into the solvent (ethanol + aquabidest), then added functional monomer (methacrylic acid), a cross-linker (ethylene glycol dimethacrylate), and an initiator (benzoyl peroxide). The pre-polymer solution was cooled in a refrigerator at -5ºC for an hour, and was heated in an oven at 75°C for 7 hours. The time is required to create a solid polymer MIP melamine with cooling-heating method is more efficient than the method use nitrogen flowing in the pre-polymer solution and then is put in a water bath and exposed to UV. Template in the polymer particles is removed by washing the polymer particles repeatedly to increase the effectiveness of cavities formation. Furthermore, MIP characterized use FTIR. The FTIR results show that the absorbance at 1000-1360 cm-1 wave number which is characteristic of the amine group wave number, for the unwashed polymer has a higher peak of 0,25 is compared with melamine MIP of 0,14. Keywords: MIP, melamine, cooling-heating, FTIR